Integração de sistemas utilizando Data Warehouse: possibilidades para sistemas de informação de controle de estoques - Favaretto, Fábio (Revista Gestão da Produção Operações e Sistemas, 2006)
Information systems (IS) are used to support decisions in many types of enterprises. These systemshave inputs that are processed and changed into outputs. These IS are not integrated when inputs are restrictedto just one enterprise activity or department. This situation restricts decisions supported by these systems.Information provided by more than one Information System can enhance decision capacity and integrate suchIS. The Data Warehouse (DW) concept was created to integrate many different IS. This paper explores somepossibilities for IS integration using DW and it is illustrated with an inventory management example. Variousintegration possibilities are shown with the purpose of enhancing information used to support decisions.Keywords: Systems Integration; Inventory Management; Information System; Data Warehouse.